Digital Marketing Business For Students of SMA Negeri 4 Bogor City - Ghanistantiono Dwi; Nuraini Purwandari; Erdiek Ardhianto; Rino Subekti; Silvana Syah; Muhammad Zulfikar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Goals in the training program This is students of SMAN 4 Bogor have knowledge , expertise and understanding in a way practical in the world of Digital Marketing, especially marketplaces and for to the front Can become a successful digital marketing entrepreneur . As for the materials in activity training This including an introduction to Digital Marketing and marketplaces as well as steps do research products in the world of Digital Marketing. Based on results observations and interviews conducted​ PKM team to power the teacher at SMAN 4 Bogor is them ( energy teacher ) wants students at SMAN 4 Bogor to also understand and understand will rapidly development technology , especially Digital Marketing. After they understand digital marketing expected they can become entrepreneur / entrepreneur in Digital Marketing. Therefore​ That held activity Devotion To the Community by Faculty Lecturers Knowledge Computer Institute Business and Informatics Kosgoro 1957 about Training Digital Marketing Business for SMAN 4 Bogor Students . Devotion method to public consists from exposure materials and training about practice about make account at one of the market places in Indonesia. The success of this program showed with liveliness all participants and enthusiastic participant do discussion and results questionnaire satisfaction show amounting to 53.3% of participants satisfied with exists training This Because can increase understanding as well as ability practical student about Digital Marketing.